Projecting line-haul truck technology adoption: How heterogeneity among fleets impacts system-wide adoption. (April 2019) - Guerrero de la Peña, Ana; Davendralingam, Navindran; Raz, Ali K.; DeLaurentis, Daniel; Shaver, Gregory; Sujan, Vivek; Jain, Neera
Abstract: A System-of-Systems engineering methodology is used to project truck technology adoption behaviors of heterogeneous fleets operating over the U.S. line-haul freight transportation system. A constrained mixed-integer linear program is formulated to optimize total cost of ownership of regional fleets given vehicle highway performance, fleet operations, cost of energy, and freight demand. A design-of-experiments demonstrates adoption sensitivity to economic parameters and individual fleet management constraints. Validation results demonstrate the importance of modeling fleet heterogeneity to achieving 90% prediction accuracy of historical adoption of three different vehicle architectures across 12 representative fleets over a 11-year period.